(untitled) (Perner’s Contacts, 2012)
This paper is focused on Ramsey pricing usage in practice, concretely Ramsey pricing nowadays has found out usage in mobile networks sector. Paper points out certain problems with implementation of this pricing into practice as well regarding also character of communications sector as network sector. Ramsey approach is used also within gradient method application for increase of operator´s economical effect and social utility considering served locality largeness.